Investigation on Morphologic Changes in the Gharanghou River Channel, on Erosive and Sedimentary Characteristics, Related to Sahand,s Dam Case Study: Gharanghou-Chay, the Eastern Slope of the Sahand Mountain (The North - West, IRAN) - maryam bayati khatibi (جغرافیا و توسعه, 2008)
Rivers are dynamic features of landscapes, whose characteristics vary over time and space related to changes in environmental controls and human impacts. The longitudinal extent of changes, their variability with time, how response the tributary to occasions, the kind of changes in mainstream cross-section, disturbance on slope in semi-arid area, are important from hydrological and geomorphological aspects. Dams, as man made structures, have major impacts on river hydrology, primarly through in the timing, magnitude, and frequency of low and high flows, ultimately producing a hydrologic artificial regime differing significantly from the pre-impoundment natural flow regime. Despite the profiles of dams on river regulation for water resources management, they create artificial flow regimes downstream and interrupt the transfer of sediments from headwater source area. These changes are started on acts of the fluvial processes at below of dams and caused adjustments of channel form. For study of effects of dams on upstream and downstream of semi-arid catchments, Gharanghou's catchment is selected. This catchment is located on the eastern slopes of Sahand Mt. This paper emphasizes the downstream effects of Sahand's dam on Gharanghou river, on the sedimentation rate of dam and also the effects of dam on downstream geomorphology. For assessing of rate of erosion, amount of sediment, evaluated method and GIS have been used then produced map of suitable area for erosion, sedimentation and landslides. The mapping is often performed through the identification and analysis instability factors. For mapping, firstly distribution map of factor produce and digitized factors then analyzed by bivariated methods and the next stage, weighted to factors and final produced hazard donation map by using Arc/View. This map shows upper part of Gharanghou's catchment erosion is critical and about of all products of erosion processes and materials of resulted by the landslides occurrence, remove into streams and the final stage, deposit in the lake of dam .The predictions show that the construction of dam will changed the longitudinal and cross of Gharanghou river's bed, rate of degradation and aggradations in Gharanghou catchment.